Systematics of a survivor: the Cambrian kingstoniid trilobite Blountia Walcott, 1916 across the Marjuman–Steptoean (Guzhangian–Paibian) extinction interval in Laurentian North America - Armstrong, Madison; Westrop, Stephen R.; Eoff, Jennifer D. (Zootaxa, 2020)
The Cambrian (Marjuman–Steptoean; Guzhangian–Paibian) kingstoniid trilobite Blountia Walcott, 1916 is distributed widely in shelf strata of Laurentian North America. Species known from Marjuman formations were lost at the mass extinction at the end of that stage. New species entered the succession during and after the extinction interval, only to disappear within the Aphelaspis Zone of the lower part of the Steptoean Stage. Steptoean species and several uppermost Marjuman (Crepicephalus Zone) species are treated in this monograph. New collections and revision of type and other archival material increase the number of species in Steptoean strata from two to six. Phylogenetic analysis supports monophyly of Blountia and Maryvillia Walcott, 1916; Blountina Lochman, in Lochman & Duncan, 1944 is retained as a monotypic taxon. Steptoean species do not form a single subclade within the cladogram, so there is no evidence for a simple monophyletic radiation following the end-Marjuman extinction. New species are Blountia angelae, B. morgancreekensis, B. nevadensis, B. newfoundlandensis, and B. tennesseensis.